Determination of Financial Distress in Food And Beverage Sector Manufacturing Companies Listed in the Indonesia Stock Exchange - Sudirman, Ganefo; Mahwiyah, Mahwiyah (JACTA: Journal of Accounting and Tax, 2023)
This study aims to analyze the factors that influence financial distress in manufacturing companies in the food and beverage industry sector in Indonesia. Factors studied include profitability, liquidity, operating capacity, and sales growth. The data used is the annual reports of companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The research method used is a quantitative method using multiple linear regression analysis. Data processing was performed using IBM SPSS 23 software. The results showed that liquidity had no significant effect on financial distress. Profitability has no significant effect on financial distress. The amount of operating profit in the current year has no significant effect on the overall financial condition of the company. The leverage factor shows a negative and significant effect on financial distress. Sales growth has no significant effect on financial distress. Acting capacity also has no significant effect on financial distress. Based on the results of this study, it was concluded that leverage is the factor that most influences financial distress in manufacturing companies in the food and beverage industry sector in Indonesia.